Improving Mathematics Learning Outcomes with The Student Team Achievement Division Model Assisted by Colored Stick Media (AJER: Advanced Journal of Education and Religion, 2024)
The application of Colored Stick Media to Mathematics subjects, especially for arithmetic addition and subtraction of integers at SD Negeri 2 Sidorejo, is motivated by the lack of students' ability to add or subtract positive and negative numbers. This study aims to determine whether the use of Colored Stick media in cooperative learning of the Student Team Achievement Division type can be used and can improve student learning outcomes at SD Negeri 2 Sidorejo. This study used a Spiral Class Action Research Technique, which was carried out in two cycles. Data processing is done using the average formula and the percentage of student success in learning. The study results of 20 students found an increase in each cycle. The pre-cycle results found that only 4 students completed with a completeness percentage of 20% in the very less category, which increased in Cycle I to 8 students who finished with a rate of 40% who entered the less class. There was a significant increase in Cycle II, with the student's level of completeness being 18 students, with a completeness percentage of 90% and falling into the very good category. From the student learning outcomes, it can be concluded that the use of colored stick media in cooperative learning of the Student Team Achievement Division type can improve student learning outcomes of SD Negeri 2 Sidorejo in the subject of Class IV Mathematics Operational Materials Count Addition and Subtraction of Integers.